2020
DOI: 10.29252/vacres.7.1.25
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Self-amplifying RNA Vaccines for Infectious Diseases and COVID-19

Abstract: In addition to conventional vaccine development for infectious diseases, nucleic acidbased vaccine approaches have recently been presented as serious alternatives to previously used strategies based on live attenuated virus particles and subunit vaccines. Particularly, RNA-based vaccines have proven attractive. In this context, immunization with messenger RNA (mRNA) has provided strong immune responses and protection against challenges with lethal doses of pathogenic viruses in vaccinated animals. Alternativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 101 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…One technology being applied in this development is the use of self-amplifying mRNA (sa-mRNA) that allows host cells to make copies of the vaccine mRNA, increasing the amount of protein produced with lower doses of administered mRNA. [11][12][13][14] Preclinical studies have shown sa-mRNA vaccines elicit a longer duration and broader activation of the immune response. 15 sa-mRNA COVID-19 vaccines were safe and immunogenic in human phase 1 studies -a dose-ranging primary vaccination study 16 and a small booster study in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…One technology being applied in this development is the use of self-amplifying mRNA (sa-mRNA) that allows host cells to make copies of the vaccine mRNA, increasing the amount of protein produced with lower doses of administered mRNA. [11][12][13][14] Preclinical studies have shown sa-mRNA vaccines elicit a longer duration and broader activation of the immune response. 15 sa-mRNA COVID-19 vaccines were safe and immunogenic in human phase 1 studies -a dose-ranging primary vaccination study 16 and a small booster study in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical and clinical applications of SAM viral vectors have proven to be efficient for vaccine development [13] . It has also been shown that recombinant SFV particles can be developed as prophylactic and therapeutic vaccine platforms against infectious diseases and various cancers since SFV-based antigen expression can induce humoral and cell-mediated immunity and have demonstrated protection against challenges with pathogens and tumor cells in animal models [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of RdRp leads to saRNA amplification in the cytoplasm 9 . Due to unique property of saRNA, high immune responses can be achieved with low doses 10 . Apart from the complex design of saRNA, its synthesis is no hard 8 .…”
Section: Introductionmentioning
confidence: 99%